Kathryn Bigelow : interviews - Bigelow, Kathryn (Conversations with filmmakers series., 2013)
With her film The Hurt Locker, Kathryn Bigelow made history in 2010 by becoming the first woman to win an Oscar for Best Director. Since then she has also filmed history with her movie about the mission to kill Osama Bin Laden. She is one of Hollywood's brightest stars, but her roots go back four decades to the very non-Hollywood, avant-garde art world of New York City in the 1970s.